2017
DOI: 10.1002/dneu.22541
|View full text |Cite
|
Sign up to set email alerts
|

Bad wrap: Myelin and myelin plasticity in health and disease

Abstract: Human central nervous system myelin development extends well into the fourth decade of life, and this protracted period underscores the potential for experience to modulate myelination. The concept of myelin plasticity implies adaptability in myelin structure and function in response to experiences during development and beyond. Mounting evidence supports this concept of neuronal activity-regulated changes in myelin-forming cells, including oligodendrocyte precursor cell proliferation, oligodendrogenesis and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 139 publications
1
69
0
Order By: Relevance
“…Additional complexity comes into view when considering that extrinsically modulated myelination can also be mediated by electrical activity and vesicular release of neurotransmitters, in particular glutamate, along unmyelinated axons (Bechler et al, ; de Faria Jr., Pama, Evans, Luzhynskaya, & Karadottir, ; Gibson et al, ). In this context, our data revealed that glutamate‐mediated activation of sodium‐dependent glutamate transporters, which are expressed by differentiating OLGs, initiates a signaling cascade that drives actin cytoskeletal changes leading to an increase in process outgrowth and branching (Martinez‐Lozada et al, ; Suarez‐Pozos, Thomason, & Fuss, ; Waggener, Dupree, Elgersma, & Fuss, ).…”
Section: The Growth Cone and Its Actin Cytoskeleton As A Driver Of Dymentioning
confidence: 99%
See 1 more Smart Citation
“…Additional complexity comes into view when considering that extrinsically modulated myelination can also be mediated by electrical activity and vesicular release of neurotransmitters, in particular glutamate, along unmyelinated axons (Bechler et al, ; de Faria Jr., Pama, Evans, Luzhynskaya, & Karadottir, ; Gibson et al, ). In this context, our data revealed that glutamate‐mediated activation of sodium‐dependent glutamate transporters, which are expressed by differentiating OLGs, initiates a signaling cascade that drives actin cytoskeletal changes leading to an increase in process outgrowth and branching (Martinez‐Lozada et al, ; Suarez‐Pozos, Thomason, & Fuss, ; Waggener, Dupree, Elgersma, & Fuss, ).…”
Section: The Growth Cone and Its Actin Cytoskeleton As A Driver Of Dymentioning
confidence: 99%
“…Within the past few years, it has been recognized that myelination likely follows a basic intrinsic program that functions in the absence of extrinsic molecular instruction. This intrinsic program is thought to be modulated by a so‐called “adaptive program” initiated by extrinsic molecular signals and/or axonal electrical activity (Bechler, Byrne, & Ffrench‐Constant, ; Bechler, Swire, & Ffrench‐Constant, ; de Faria Jr., Pama, Evans, Luzhynskaya, & Karadottir, ; Foster, Bujalka, & Emery, ; Gibson, Geraghty, & Monje, ). Thus, the regulation of myelination via the action of extracellular factors, here referred to as “extrinsically modulated myelination,” could be considered a form of “adaptive” myelination.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, shortening of the internodes is associated with significant reduction of conduction velocity in the optic nerve (Etxeberria et al, ). Changes in oligodendrogenesis and/or myelination have also been observed in many other paradigms where the alterations of neuronal activity may be more complex than simple reduction or increase (reviewed by Almeida & Lyons, ; Forbes & Gallo, ; Gibson, Geraghty, & Monje, ). Therefore, a simple concept stating that increased neuronal activity enhances myelination, while decreased neuronal activity reduces myelination most likely does not apply, and modulation of myelination by neuronal activity may be neuronal circuit specific and may involve multiple mechanisms.…”
Section: Functional Role Of Glutamate Receptors and Glutamatergic Sigmentioning
confidence: 99%
“…Myelin growth is a fast process in which oligodendrocyte mass multiplies in just a few days 3 . In mammals, myelination begins around birth and OPCs are maintained throughout life; myelination in the cortex of the adult brain is thought to contribute to learning and higher brain functions 4 . Orchestrating timely OPC generation, oligodendrocyte differentiation and energy-demanding myelin synthesis under changing metabolic conditions and in phases of physiological lowoxygen levels 5 is a major challenge.…”
mentioning
confidence: 99%